Buddha, the Trimurti, and modern Hinduism - Kulkarni, Anant Ramchandra, 1897- (Kulkarni, 1980)
Study of the life and teachings of Gautama Buddha and presentation of the thesis that Hinduism and Buddhism, in their original forms, are not much different.